A case of nearly mistaken AB para-Bombay blood group donor transplanted to a group 'O' recipient. (31st October 2014) - Townamchai, Natavudh; Watanaboonyongcharoen, Phandee; Chancharoenthana, Wiwat; Avihingsanon, Yingyos
Abstract : Unintentional ABO mismatch kidney transplantation can cause detrimental hyperacute rejection. We report the first successful ABO incompatible kidney transplantation from an AB para-Bombay donor to O recipient. At the initial evaluation, the donor's ABO type was discordance on the cell typing and serum typing, which typed to be 'O' as cell typing and 'AB' as serum typing. At the second investigation, it was confirmed that the donor had a unique, rare but not uncommon blood type AB para-Bombay which was incompatible with the recipient's blood group. The kidney transplantation was successfully performed by an ABO incompatible preconditioning, double filtration plasmapheresis (DFPP) and rituximab. The serum creatinine at 12 months post-transplantation was 1.3 mg/dL. The pathology of the kidney biopsy showed no signs of rejection.